Qualitative and Quantitative Picture of Innovation in Russia - Guzikova, Liudmila (Information Management and Business Review, 2014)
In the paper the general characteristic of innovative activity in Russia is given, the factors of innovation are identified; the performance indicators of innovation are determined; the qualitative relations between the factors and performance indicators of innovation are identified; the models of quantitative analysis of relation between the factors and performance indicators of innovation are proposed; the proposed models are applied to receive quantitative characteristics; the current state, prospects and development priorities of innovation in Russia are assessed.